2015
DOI: 10.1128/aac.00177-15
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ceftiofur Injection on Gut Microbiota and Escherichia coli Resistance in Pigs

Abstract: Resistance to extended-spectrum cephalosporins (ESCs) is an important health concern. Here, we studied the impact of the administration of a long-acting form of ceftiofur on the pig gut microbiota and ESC resistance in Escherichia coli. Pigs were orally inoculated with an ESC-resistant E. coli M63 strain harboring a conjugative plasmid carrying a gene conferring resistance, bla CTX-M-1 . On the same day, they were given or not a unique injection of ceftiofur. Fecal microbiota were studied using quantitative PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 31 publications
(28 reference statements)
0
21
1
Order By: Relevance
“…Bearing this in mind, we decided to evaluate the impact of the oral administration of E. coli strains on the excretion of ESCR Enterobacteriaceae in feces and their survival in manure through an experimental model of ESCR E. coli infection (16). The E. coli M63 strain used in this model seemed to be very well suited to the pig microbiota and persisted in all groups up to the end of the trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bearing this in mind, we decided to evaluate the impact of the oral administration of E. coli strains on the excretion of ESCR Enterobacteriaceae in feces and their survival in manure through an experimental model of ESCR E. coli infection (16). The E. coli M63 strain used in this model seemed to be very well suited to the pig microbiota and persisted in all groups up to the end of the trials.…”
Section: Discussionmentioning
confidence: 99%
“…This isolate, named UB12/059-3, was then made resistant to rifampin and used as a receptor for in vitro conjugation with an ESCR E. coli isolate obtained from a healthy pig at a slaughterhouse and previously shown to contain a bla CTX-M-1 gene. The resulting transconjugant, E. coli M63, belongs to the B1 phylogenetic group and contains resistance genes bla CTX-M-1 , bla CMY-59 , aadA5, sul2, and dfrA17 (16). It is resistant to cefotaxime, rifampin, streptomycin, and trimethoprim-sulfamethoxazole.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four different trials were conducted in 2012 to 2013, using the previously described ESBL-producing E. coli M63 strain (5). The experiments were performed in accordance with French animal welfare regulations, and the protocols were approved by the ANSES/ENVA/UPEC ethics committee (ComEth approval no.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, E. coli M63 was obtained by conjugation between a randomly chosen pansusceptible E. coli isolate, UB12/059-3, obtained from a specific-pathogen-free pig of our herd, made resistant to 250 mg/liter rifampin, and an ESC-resistant E. coli isolate, 05-M63-1, from our slaughter pig strain collection. Thus, E. coli M63 is resistant to rifampin because of chromosomal mutations, and sequencing of the ESC resistance plasmid showed that it was an IncI1/ST12 plasmid harboring the bla CTX-M-1 , bla CMY-2 , sul2, dfrA17, and aadA5 genes (5). The E. coli M63 cultures used for pig inoculation were prepared in cefotaxime (CTX)-supplemented medium.…”
Section: Methodsmentioning
confidence: 99%